Color Characteristics of Four-Color Samples in the Foggy Environment under Different Lighting Conditions. Issue 2 (April 2021) - Cui, Ganggang; Zhou, Xiaoli; Qian, Yong; Zhang, Zheqian; Liu, Muqing
Abstract: Traffic signs should provide clear signals for drivers and passengers under various environmental and geographic conditions. In foggy weather, the signal will be disturbed due to light scattering, which will cause obstacles to recognition. This study simulated a foggy environment in the laboratory, used a standard color card as the target, and introduced a colorimeter to record the color coordinates, then calculated the color difference and analyzed the four-color samples' color properties in different lighting conditions. We found that as the relative visibility increases, the chromatic aberration of the sample will gradually decrease under different lighting conditions and reach zero when the relative visibility is higher than 70%. We found that the green and blue samples have better color coordinate retention capabilities than the fog's red and yellow. We compared all tested light sources' performance, and the results showed that 3000K LED and incandescent lamps are better than other light sources. This study will provide a data basis for the study of traffic safety and accident prevention.